The Analysis of the Meaning in The Poem Fire and Ice by Robert Frost - Putu Ninda Yuliana (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to analyze the prose meaning and the total meaning contained in the poem â€œFire and Iceâ€ by Robert Frost. The writer relates other intrinsic elements (Symbol, Paradox, Denotation, and Connotation) to support and strengthen the meaning contained in the poem â€œFire and Iceâ€. The intrinsic elements that used have also been analyzed. After the writer analyzes all these elements, the elements are interrelated to form a poem. Something that makes this poem interesting is that all the elements discussed are able to support the meaning of the poem and interconnected to form a unified meaning. By knowing these elements, we can capture the whole meaning of the poem.